Analisis Semesta Narasi Gundala Melalui Pendekatan Narrative Braid dan Transmedia Storytelling - Aditya Satyagraha (ULTIMART Jurnal Komunikasi Visual, 2022)
The year 1960-1970 was the golden era of classic Indonesian cergam, there are many Indonesian superheroes born on the cergam such as Sri Asih, Godam, and Gundala Putra Petir. But Indonesian cergam stagnated and decreased readership, until in 2003, publisher Bumilangit restored the classic cergam indonesian superhero. In its journey Bumilangit managed to acquire and obtain commercial rights from more than 1000 classic Indonesian cergam superhero characters. All the characters are restored and collected in one universe (canon) called Jagat Bumilangit. One of the characters who has changed from the narrative is Gundala. The research method used is qualitative descriptive to get the data to be processed to be simplified into one form of transmedia model. Where this research focuses on the relationship of Gundala characters with his storyworld, namely Jagat Bumilangit, as well as the relationship of Gundala and other characters so as to help strengthen the storyworld of jagat Bumilangit and also how to develop Gundala character content strategy into multiplatform through narrative braid and transmedia storyworld approaches. Through this research, the author came to the conclusion that the development of the narrative universe (storyworld) in jagat Bumilangit is something refreshing for the Indonesian superhero world. But still need consistency in maintaining the narrative in a space that can be trusted by the audience in studying and looking for other original content that is more cohesive and able to enrich the preservation of their data about Gundala and the Universe bumilangit universe not only from the big screen film alone. Keywords: bumilangit; gundala; comic; transmedia; storyworld.